Memaknai Simbol-Simbol Religius Injil Yohanes - Petrus Lakonawa (Bina Nusantara University, 2014)
Gospel of John is the most symbolic Gospel in the official collection of the New Testament scriptures. Its symbolical characterestic thus poses challenges to the readers as to not approaching it in the mere literal sense but to dig into its implied meaning behind. Viewing it in this line, the question we would usually face is that of what is the real meaning of the symbols in the Gospel of John and how could we achieve such meaning. In this article, the author seeks to demonstrate some of the symbolical characterics of the Gospel of John and to discuss some of the hermeneutical approaches that can be utilized for the sake of such interpretion. This article would argue that to obtain a thorough meaning we need to identify and uncover all the various dimensions of meaning contained therein.